Flipped classroom and creative learning resources for teaching history - Molina-Torres, María Pilar; Pastor Blázquez, María Montserrat (Creativity Studies, 2024)
The study aims to analyse the perceptions and pedagogical skills of university students in the implementation of the flipped classroom in the degree of primary education. The sample consists of 209 students following the bilingual English programme at the University of Córdoba, Spain. The study is described as a non-experimental quantitative research, which means that it focuses on the collection and analysis of data without intervention or manipulation of variables. A fifteen-item Likert-type questionnaire was used to collect the data. The questionnaire appears to be on a scale of 1 to 5, where participants rate their answers according to the options given. The findings suggest that new electronic learning strategies need to be incorporated into teaching methodology. There is an emphasis on the importance of providing practical approaches to digital teaching and didactic resources. Students have shown a positive attitude towards their training needs, particularly in consolidating historical thinking and integrating active learning methods with good teaching practice.